Rancang Bangun Smart Doorlock Kamar Mesin dan Anjungan Berbasis RFID dan Arduino - Thariq Arifun Nathiq (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research develops a smart doorlock system for engine rooms and platforms based on RFID technology and the Arduino platform. This system is designed to increase security and efficiency in managing access to important areas on a ship or industrial installation. The method used involves the integration of an RFID module as an authentication medium and an Arduino microcontroller as the system control center. Users can open the door simply by holding the registered RFID card close to the RFID reader, which then sends a signal to the Arduino to activate the door lock mechanism. This system is also equipped with an access data recording feature that allows real-time monitoring and review of incoming and outgoing activities. Test results show that the system functions well in various scenarios, demonstrating high reliability and responsiveness. Thus, this RFID and Arduino based smart doorlock system can be an effective solution in improving security and access control in critical environments.